2008
DOI: 10.1007/s12289-008-0311-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Mold Surface Coatings in Injection Molding. Application to the Ejection Stage.

Abstract: Mold surface coatings are used in thermoplastics injection molding to increase lifespan of the mold before maintenance. Development of coating processes such as PVD (Phase Vapor Deposit) and PACVD (Plasma Assisted Chemical Vapor Deposit) allowing thin coatings manufacturing gives access to new application fields. Investigated coatings were Chromium nitrium (CrN), Titane nitrium (TiN), Diamond like Carbon (DLC), glassy deposit (SiOx), Chromium and polished steel. This work intended to study the impact of those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 5 publications
0
19
0
2
Order By: Relevance
“…outil soit ex situ à partir d'équipements spécifiques de laboratoire [75], soit in situ dans le moule en équipant un éjecteur d'un capteur de force [76]. Peter Jones [77], dans un procédé d'injection classique, propose de prendre en compte le coefficient de friction, les propriétés mécaniques du polymère, le retrait et les dimensions de la pièce pour calculer la force nécessaire à l'éjection de la pièce, F é , telle que :…”
Section: Dépôts Cvd Et Pacvdunclassified
“…outil soit ex situ à partir d'équipements spécifiques de laboratoire [75], soit in situ dans le moule en équipant un éjecteur d'un capteur de force [76]. Peter Jones [77], dans un procédé d'injection classique, propose de prendre en compte le coefficient de friction, les propriétés mécaniques du polymère, le retrait et les dimensions de la pièce pour calculer la force nécessaire à l'éjection de la pièce, F é , telle que :…”
Section: Dépôts Cvd Et Pacvdunclassified
“…The absence of a unique selection of parameter levels to optimize demolding behaviour for the surface treatment and polymers investigated was highlighted. Charmeau et al (2008) investigated the effect of coatings on the mold surface in order to reduce the occurrence of weldlines in polymer parts and concluded that the contact thermal resistance associated with the coating was the dominant parameter. Ejection forces were evaluated and the impact was then studied through ejection work and friction coefficients.…”
Section: Optimise Wettability/surface Energies (Including Surface Coamentioning
confidence: 99%
“…A study of F* in regards to applied mould surface treatments showed that the efficiency of the coatings depended on the polymer used, its shrinkage nature, and the roughness of the coated surface [24]. Griffiths et al reported defects on PC moulded parts (Fig.…”
Section: Introductionmentioning
confidence: 99%